Pelatihan Pengolahan dan Visualisasi Data Penduduk menggunakan Python - Junaidi, Satrio; Devegi, Mourend; Kurniawan, Haris (LPPM Universitas Bumigora, 2023)
Imitations of officers in analyzing and visualizing data in Tabing Banda Gadang Village Head. Most of these problems are caused by the lack of knowledge and expertise of the apparatus as well as the limited number of computers. The data at the Tabing Banda Gadang Village Head are not stored properly, the data is stored in Excel and there is no technology-assisted data management and data presentation. Implementation method by providing training and mentoring. The training provided is in the form of basic skills in using Python in data visualization. Its activities include training and mentoring Data Visualization and data processing using the Python program at Tabing Banda Gadang Urban Village. The implementation of community service conducted interviews and administered questionnaires to find out the extent to which the trainees understood the use of Python software. The service team explains data visualization accurately and concisely. District employees are assisted in understanding and processing data using this Anaconda Jupyter Python Notebook. District officers find it helpful in their work with the applications taught.